PENGARUH PERTIMBANGAN, PENGETAHUAN, SIKAP NASABAH TERHADAP KEPUTUSAN NASABAH MEMILIH PRODUK BANK SYARIAH DI KOTA DENPASAR - Miko Andi Wardana (Forum Manajemen STIMI Handayani Denpasar, 2016)
The impact of customer knowledge and customer consideration to thecustomer’s decision to choose products Islamic banks through customer attitudesas an intervening variable. From the preliminary data of empirical research showsthere is a phenomenon with respect to customers of Islamic banks in Bali. Thepurpose of this study was to determine directly or indirectly influence the customerknowledge and consideration of consumers towards the customer’s decision to chooseproducts of Islamic banks in Denpasar through customer attitudes, this research isa quantitative research survey approach, with a sample of 100 respondents. The testinstrument by using validity and reliability test while the data used are primary andsecondary data. Analysis technique used is path analysis.From the analysis by using path analysis, calculation results obtained showedthat customer knowledge variables significantly influence customer attitudes withcoefficient Standarrdized 0.452 with probability t sig 0,000 or sig <0.05, customerconsideration variables significantly influence customer attitudes to the valueStandarrdized coefficient of 0.393 with a probability t sig 0,000 or sig <0.05,customer knowledge but tidah significant positive impact on the customer’s decisionStandarrdized coefficient of 0.067 with a probability t sig 0.496 or sig> 0.05, apositive influence customer consideration and significant impact on the customer’sdecision Standarrdized coefficient of 0.316 with a with probability t sig 0,001 orsig<0.05, customer attitude positive and significant impact on the customer’s decisionStandarrdized coefficient of 0.354 with a with probability t sig 0,002 or sig < 0.05.